2018
DOI: 10.1093/ntr/nty259
|View full text |Cite
|
Sign up to set email alerts
|

A Machine-Learning Approach to Predicting Smoking Cessation Treatment Outcomes

Abstract: Aims Most cigarette smokers want to quit smoking and more than half make an attempt every year, but less than 10% remain abstinent for at least 6 months. Evidence-based tobacco use treatment improves the likelihood of quitting, but more than two-thirds of individuals relapse when provided even the most robust treatments. Identifying for whom treatment is effective will improve the success of our treatments and perhaps identify strategies for improving current approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 33 publications
1
73
0
Order By: Relevance
“…Some examples included prediction of postoperative in-hospital mortality [ 16 ], complications in patients with diabetes mellitus [ 17 ], and occurrence of cardiovascular diseases in patients on dialysis [ 18 ]. For smoking cessation, a decision tree model developed with machine learning to predict smoking cessation treatment outcome was proposed by Coughlin et al in 2018 [ 19 ]. The study included 161 participants, with 90 in the training dataset and 71 in the validation dataset, yielding an average correct classification rate of about 64%.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples included prediction of postoperative in-hospital mortality [ 16 ], complications in patients with diabetes mellitus [ 17 ], and occurrence of cardiovascular diseases in patients on dialysis [ 18 ]. For smoking cessation, a decision tree model developed with machine learning to predict smoking cessation treatment outcome was proposed by Coughlin et al in 2018 [ 19 ]. The study included 161 participants, with 90 in the training dataset and 71 in the validation dataset, yielding an average correct classification rate of about 64%.…”
Section: Introductionmentioning
confidence: 99%
“…In the study on treatment response to CBT, Reggente et al (2018) observed an accuracy of 67% for predicting response in OCD patients. In a similar vein, Coughlin et al (2018) found that fMRI characteristic could predict the treatment response to GCBT in cigarette smokers. Our finding with an accuracy rate of 67.8% is in the range of previous reports.…”
Section: Discussionmentioning
confidence: 83%
“…In recent years, few experts have contended that machine learning techniques have been successfully employed to build a prediction of the success of smoking cessation. However, model interpretability tends to be disregarded in those existing studies [29][30][31] in terms of their complex black-box system. Accordingly, common decision-making responses suffer from the class imbalance problem due to overwhelming skewed distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a limited amount of studies [29][30][31] demonstrated that machine learning classifiers, such as decision tree, SVM, and MLP have the potential to substitute statistical methods in constructing the prediction models of smoking cessation. Coughlin et al [29] presented the prediction model of smoking quit outcomes to improve the success of evidence-based tobacco use treatment and current methods. The significant features were selected by generalized estimating equations followed by using decision tree classifier to identify the smoking quit prediction.…”
Section: Literature Reviewmentioning
confidence: 99%